Mathematical modeling of the radial crossflow hollow fiber membrane module for multi-component gas separation - Lock, S.S.M. (Trans Tech Publications Ltd, 2014)
A âMulti-component Progressive Cell Balanceâ approach has been applied to characterize the gas separation of the radial crossflow hollow fiber membrane module. The mathematical model is an indispensable tool to evaluate the separation performance of membrane material towards different components. The approach is required to be implemented since there is scarcely available mathematical model to characterize the two dimensional radial crossflow. In addition, the currently available mathematical model is confined to the ideal binary system, which constraints its applicability in real membrane separation process with many components. The significance of the developed multi-component mathematical model as compared to the model adapting the ideal binary simulation condition is demonstrated in this study. Â© 2014 Trans Tech Publications, Switzerland.